Retinal nerve fibre layer thickness and contrast sensitivity in HIV-infected individuals in South Africa: a case-control study. - Sophia Pathai; Stephen D Lawn; Helen A Weiss; Colin Cook; Linda-Gail Bekker; Clare E Gilbert (PLoS ONE)
Background Antiretroviral treatment (ART) has altered the spectrum of HIV-related eye disease, resulting in a lower prevalence of retinal opportunistic infections (OIs). However, abnormalities in visual function have been reported in HIV-infected individuals despite effective viral suppression and the absence of retinal OIs. These changes may be mediated by an HIV-associated 'neuroretinal disorder', characterized by changes in the retinal nerve fibre layer (RNFL). HIV infection may also be associated with accelerated biological aging. The aim of this study was to investigate the relationships between contrast sensitivity, RNFL thickness, HIV infection and frailty in South African adults. Methods Case-control study of 225 HIV-infected individuals without retinal OIs and 203 gender/age-matched HIV-seronegative individuals. Peri-papillary RNFL thickness was determined with spectral domain optical coherence tomography in four quadrants. CS was measured using a Pelli-Robson chart. Frailty was assessed using standard criteria. Multivariable linear and logistic regression were used to assess associations between HIV status and RNFL/CS and frailty. Results The median age of both groups was similar (41.2 vs. 41.9 years, p = 0.37). 88% of HIV-infected individuals were receiving ART and their median CD4 count was 468 cells/μl. Adjusted CS score was lower in HIV-infected participants compared to HIV-seronegative individuals (1.76 vs. 1.82, p = 0.002). Independent predictors of poor CS in the HIV-infected group were positive frailty status and current HIV viral load >2 log copies/ml. Lower CS score was also associated with thin temporal RNFL in HIV-infected individuals (p = 0.04). Superior quadrant RNFL thickness was greatest in ART-naïve participants relative to the HIV-uninfected group (p-trend = 0.04). Longer ART duration was associated with thinning of inferior and nasal RNFL quadrants (p-trend = 0.03 and 0.04, respectively). Conclusions Contrast sensitivity is reduced in HIV-infected individuals and functionally associated with frailty and unsuppressed viraemia. This may reflect structural changes in the RNFL that are evident despite the absence of OIs.